2021
DOI: 10.3390/rs13061208
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Latest GPM IMERG V06 Early, Late and Final Precipitation Products across China

Abstract: This study evaluated the performance of the early, late and final runs of IMERG version 06 precipitation products at various spatial and temporal scales in China from 2008 to 2017, against observations from 696 rain gauges. The results suggest that the three IMERG products can well reproduce the spatial patterns of precipitation, but exhibit a gradual decrease in the accuracy from the southeast to the northwest of China. Overall, the three runs show better performances in the eastern humid basins than the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…For IMC the ability of the satellite product to detect and quantify rainfall was not much different for elevations (the highest elevation of rain gauge station was 1260 m) (Figure 10). consistent with previous studies which found similar results for stations below 2000 m [40,82,83].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For IMC the ability of the satellite product to detect and quantify rainfall was not much different for elevations (the highest elevation of rain gauge station was 1260 m) (Figure 10). consistent with previous studies which found similar results for stations below 2000 m [40,82,83].…”
Section: Discussionsupporting
confidence: 93%
“…Lower CC values in hills were followed by higher RMSE and RB values (Figure 10c), consistent with those found in Cyprus [82]. A decrease in the correlation of IMERG and rain gauge data with increasing elevation was also found across China [83]. Hence, daily rainfall observations using IMERG data in the hills still needs an improvement.…”
Section: Effect Of Topographysupporting
confidence: 81%
“…For precipitation, we use the Integrated Multi-satellite Retrievals for the Global Precipitation Measurement (GPM IMERG) final product (Huffman et al, 2015). While we select the GPM IMERG final product which shows superior performance compared to other products (Beck et al, 2019) without shortening the study period, the results need to be considered in the context of performance and uncertainty of the data presented in existing evaluation studies (O et al, 2017;Yu et al, 2021). For precipitable water, we focus on the Atmospheric Infrared Sounder (AIRS; AIRS Project, 2019), utilizing four additional reanalyzes data sets to check consistency in the results, these being the second Modern-Era Retrospective Analysis for Research and Applications (MERRA2; Gelaro et al, 2017); European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis version 5 (ERA5; Hersbach et al, 2020); the Japanese 55-year Reanalysis (JRA-55) Kobayashi et al (2015); and the National Centers for Environmental Prediction (NCEP; Saha et al, 2010Saha et al, , 2014.…”
Section: Datamentioning
confidence: 99%
“…(4) The Global Precipitation Measurement (GPM) Integrated Multi-satellite Retrievals for GPM (IMERG) Final Precipitation L3 Half Hourly 0.1-degree × 0.1-degree V06 (GPMI) [54]. The data set applies the unified algorithm that provides rainfall estimates by combining data from all of the passive-microwave instruments in the GPM Constellation, performs well in the lower reaches of the Yangtze River [55], and has a better capture of the actual variation tendency of hourly precipitation in extreme precipitation events [56].…”
Section: Observation Datamentioning
confidence: 99%